2008
DOI: 10.1111/j.1365-2427.2008.01991.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to ship‐induced waves of benthic invertebrates in various littoral habitats

Abstract: Summary 1. Ship‐induced waves disturb benthic invertebrate assemblages colonizing littoral zones of lakes and rivers. However, the impact of ship‐induced waves on invertebrates has rarely been quantified, and the influencing factors have not been addressed. 2. In an experimental wave tank, five benthic invertebrate species, Bithynia tentaculata, Calopteryx splendens, Dikerogammarus villosus, Gammarus roeseli and Laccophilus hyalinus, were exposed to waves of increasing shear stress (0.43–2.19 N m−2). Mean numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 24 publications
6
46
0
Order By: Relevance
“…The a priori predictions of the effects of cargoship traffic addressed two potentially related stressors for riverine invertebrates: the importation of taxa from elsewhere (Ricciardi, Serrouya & Whoriskey, 1995;Tamburri, Wasson & Matsuda, 2002) and the production of disturbing waves (Petran, 1977). These stressors should affect trait categories favouring biological invasions (Statzner, Bonada & Dolédec, 2008b) or wave resistance (Gabel et al, 2008), respectively. Therefore, predicted that cargo-ship traffic should increase the frequency of trait categories that facilitate the foundation of new populations: long life cycles ( ‡semivoltine), several reproductive cycles per individual, reproduction by single individuals, hermaphroditism, bud production and ⁄ or ovoviviparity.…”
Section: Unravelling the Simultaneous Action Of Multiple Stressorsmentioning
confidence: 99%
“…The a priori predictions of the effects of cargoship traffic addressed two potentially related stressors for riverine invertebrates: the importation of taxa from elsewhere (Ricciardi, Serrouya & Whoriskey, 1995;Tamburri, Wasson & Matsuda, 2002) and the production of disturbing waves (Petran, 1977). These stressors should affect trait categories favouring biological invasions (Statzner, Bonada & Dolédec, 2008b) or wave resistance (Gabel et al, 2008), respectively. Therefore, predicted that cargo-ship traffic should increase the frequency of trait categories that facilitate the foundation of new populations: long life cycles ( ‡semivoltine), several reproductive cycles per individual, reproduction by single individuals, hermaphroditism, bud production and ⁄ or ovoviviparity.…”
Section: Unravelling the Simultaneous Action Of Multiple Stressorsmentioning
confidence: 99%
“…Structural complexity or high spatial heterogeneity is typically correlated with high densities (Lewin et al 2004;Kostylev et al 2005) or species richness (Moon 1934;Le Hir and Hily 2005;Kostylev et al 2005;Moschella et al 2005;Brauns et al 2007) of aquatic invertebrates. Just as with fish, structurally complex shore zones protect invertebrates from the damaging forces of waves (Gabel et al 2008). On the terrestrial side of the shore zone, Paetzold et al (2008b) found that channelization, which simplifies the structure of the shore zone, reduced abundance and richness of terrestrial arthropods, and some vertebrates preferentially use complex shore zones (e.g., Stickney et al 2002).…”
Section: Physical Complexitymentioning
confidence: 99%
“…However, at high turbulence levels, prey capture success becomes hampered (MacKenzie et al 1994), leading to a domeshaped response of fish foraging success to turbulence. In an analogous context, waves in the littoral zone may increase the encounter rate of food items, with benthivorous fish reaping a particular benefit as macroinvertebrates are resuspended by waves (Gabel et al 2008), which may increase their conspicuity and accessibility to fish.…”
Section: Introductionmentioning
confidence: 99%